Peramalan Ekspor Minyak Kelapa Sawit Indonesia Menggunakan Metode Pemulusan Eksponensial Tripel Tipe Brown - Istima Istima; Media Rosha; Meira Parma Dewi (Journal of Mathematics UNP, 2021)
Abstract – Palm oil is one of the non oil and natural gas export commodities in Indonesia that has a high economic value and becomes one of the country’s foreign exchange earner. The increase of the world market needs of palm oil will certainly affect export activities. Therefore, the exports of palm oil for the next few years need to be predicted so that the government can make planning and do appropriate actions. The method used was the Tripel Exponential Smoothing Method Type Brown. This method is a one parameter quantitative forecasting method for time series data that are quadratic trend. The forecast accuracy measure used was Mean Square Error (MSE) to determine the ideal parameter. The forecast model obtained was . The forecast of the exports of Indonesian palm oil in 2015 to 2019 were between 24.509,329 thousand tons to 33.563,659 thousand tons. Keywords – forecasting, export, palm oil, tripel exponential smoothing method type brown